Provenance as an Ethical Measure for the Archival Knowledge Organization of Photographs - Machado, Bruno Henrique [UNESP]; Semidão, Rafael; De Carvalho Madio, Telma Campanha [UNESP]; Martínez-Ávila, Daniel (My University, 2020)
This paper reflects on the use of the principle of provenance in the archival knowledge organization of photographs as a critical an ethical measure to fight their misuses. It discusses the concept of provenance from a pragmatist and domain-analytic perspective to assess the potential of this principle in the determination of the contextual information of photographs to counteract fake news.